Teori Pengurangan Ketidakpastian - Winda Kustiawan; Nabillah Miftahul Jannah (Maktabatun: Jurnal Perpustakaan dan Informasi, 2021)
Things that often appear in social phenomena are dialogue and maintaining relationships. Humans become creatures that have a sizable social movement in an effort to fulfill needs and must be able to adapt in an asynchronous social environment. In this environment, of course, it can make someone encounter situations that have never been encountered and of course that is full of uncertainty, that is, humans are required to be able to create interpersonal communication to try to get information so that life can continue. The theory of reducing uncertainty in a dialogue as well as forming relationships and maintaining a ready correlation. Which is this theory, putting all individuals in new positions or also using other people's conversations by trying to find the substance of the ongoing conversation. This theory is most important so that someone can shape the existing tactics when dealing with that situation as a result of which uncertainty and anxiety can be seen very well. This theory describes the state, preparation, then builds a correlation of one's strengths that unite on the right speech. And also that's what makes a person free from communication problems that put a person in uncertainty and anxiety.